2010
DOI: 10.1002/prca.201000035
|View full text |Cite
|
Sign up to set email alerts
|

The absolute quantification of eight inter‐α‐trypsin inhibitor heavy chain 4 (ITIH4)‐derived peptides in serum from breast cancer patients

Abstract: The obtained results particularly suggest potential for these ITIH(4)-derived peptides in the follow-up of breast cancer after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…ITIH4, a protein secreted by the liver in times of trauma and involved in the acute-phase response, was shown to have a downward trend as the amount of n-3 fatty acids increased in the dietary groups. In serum from breast cancer patients it was shown that this protein as peptide fragments was upregulated in comparison to healthy controls (46,47). ITIH4 has also proposed to be cleaved by plasma kallikrein in cancers such as ovarian and breast (47,48) which could possibly explain the bands seen at 120 kDa (data not shown) and 100 kDa.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ITIH4, a protein secreted by the liver in times of trauma and involved in the acute-phase response, was shown to have a downward trend as the amount of n-3 fatty acids increased in the dietary groups. In serum from breast cancer patients it was shown that this protein as peptide fragments was upregulated in comparison to healthy controls (46,47). ITIH4 has also proposed to be cleaved by plasma kallikrein in cancers such as ovarian and breast (47,48) which could possibly explain the bands seen at 120 kDa (data not shown) and 100 kDa.…”
Section: Discussionmentioning
confidence: 92%
“…In serum from breast cancer patients it was shown that this protein as peptide fragments was upregulated in comparison to healthy controls (46,47). ITIH4 has also proposed to be cleaved by plasma kallikrein in cancers such as ovarian and breast (47,48) which could possibly explain the bands seen at 120 kDa (data not shown) and 100 kDa. Thus, the downward trend of the expression is consistent with chemoprevention.…”
Section: Discussionmentioning
confidence: 92%
“…There are a few reports that proposed this protein as an OC marker [37, 42]. Changes in the levels of ITIH4-derived peptides were also observed in urine of early prostate cancer patients [43] and in the serum of breast cancer patients [44] and gastric adenocarcinoma patients [41]. A correlation was also suggested between different fragmentation of ITIH4 and disease conditions [45].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Serum ITIH4 proteolytic fragments resulting from proteolytic processing of the PRR are also of interest due to their cancer biomarker potential. 2022 …”
Section: Introductionmentioning
confidence: 99%